Detection of Dirofilaria immitis and other arthropod-borne filarioids by an HRM real-time qPCR, blood-concentrating techniques and a serological assay in dogs from Costa Rica - Montenegro, Víctor M. (2015)
Background: Canine filarioids are important nematodes transmitted to dogs by arthropods. Diagnosis of canine filariosis is accomplished by the microscopic identification of microfilariae, serology or PCR for filarial-DNA. The aim of this study was to evaluate a molecular assay for the detection of canine filariae in dog blood, to compare its performance to other diagnostic techniques, and to determine the relationship between microfilarial concentration and infection with other vector-borne pathogens. Methods: Blood samples from 146 dogs from Costa Rica were subjected to the detection of canine filarioids by four different methods: the microhematocrit tube test (MCT), Knott's modified test, serology and a high resolution melt and quantitative real-time PCR (HRM-qPCR). Co-infection with other vector-borne pathogens was also evaluated. Results: Fifteen percent of the dogs were positive to Dirofilaria immitis by at least one of the methods. The HRM-qPCR produced distinctive melting plots for the different filarial worms and revealed that 11.6% of dogs were infected with Acanthocheilonema reconditum. The latter assay had a limit of detection of 2.4x10-4 mf/μl and detected infections with lower microfilarial concentrations in comparison to the microscopic techniques and the serological assay. The MCT and Knott's test only detected dogs with D. immitis microfilaremias above 0.7 mf/μl. Nevertheless, there was a strong correlation between the microfilarial concentration obtained by the Knott's modified test and the HRM-qPCR (r = 0.906, p < 0.0001). Interestingly, one dog was found infected with Cercopithifilaria bainae infection. Moreover, no association was found between microfilaremia and co-infection and there was no significant difference in microfilarial concentration between dogs infected only with D. immitis and dogs co-infected with Ehrlichia canis, Anaplasma platys or Babesia vogeli. Conclusions: This is the first report of A. reconditum and C. bainae in Costa Rica and Central America. Among the evaluated diagnostic techniques, the HRM-qPCR showed the most sensitive and reliable performance in the detection of blood filaroids in comparison to the Knott's modified test, the MCT test and a serological assay.